Development of Doe'ku Application: A Digital Solution to Manage Personal Finance Effectively - Nur Annafiah; M. Miftach Fakhri; La Ode Lisbar; Amelia Syamsuddin; Nur Yahya Akhmad; Aprilianti Nirmala S (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The development of the Doe'ku application aims to provide an effective digital solution for managing personal finances. The application is designed to improve users' financial literacy through various features, such as transaction records, budget setting, savings plans, and scheduled transactions. This study utilizes the prototype model software development method, which allows for continuous interaction between developers and users during the application creation process. The results show that the Doe'ku application can assist users in effectively monitoring and managing their finances. User evaluations showed that the application provides an optimal user experience with an intuitive and responsive interface. In addition, the application is designed to be accessible and easy to operate, meeting both the functional and nonfunctional needs of users. As such, the Doe'ku application is expected to contribute significantly to improving users' financial literacy and personal financial management capabilities.